Bioethanol Production as Renewable Energy from Macroalgae Eucheuma cottonii: A Mini Review - Rasyid, Rahimsyah Ijas Nur; Muhammad Fadhlan Dzikri; Hayya Laudza Adani; Evelyna Anindya Davina (Universitas Negeri Semarang, 2024)
Energy demand has increased from several years ago due to economic growth and population increase. Meanwhile, non-renewable energy reserves from fossil fuels are dwindling. Bioethanol is one alternative energy resource to substitute fossil fuels and their derivatives. The fast expansion and environmental friendliness of Eucheuma cottonii macroalgae's growth make it a promising contender for use as a sustainable renewable energy source. Because of its abundant carbohydrate content, it can be utilized in generating bioethanol. This analysis delves into the potential of macroalgae in bioethanol production by concentrating on hydrolysis and fermentation. The Eucheuma cottonii process involved hydrolyzing it into reducing sugars using an optimal dilute acid hydrolysis pretreatment. This hydrolysate is converted into bioethanol by Saccharomyces cerevisiae through fermentation. Process the bioethanol obtained is distilled to reach the maximum concentration. The process of producing bioethanol, which is a renewable energy source, is expected to have an important impact on dealing with the energy crisis and advancing environmental sustainability.